2000
DOI: 10.1063/1.126627
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of ultrashallow p+/n junction by 248 nm excimer laser and rapid thermal processing with different preamorphization depths

Abstract: Ultrashallow p+/n junctions formed by B+-ion implantation and annealed by spike rapid thermal annealing (RTA) or laser annealing were studied. The effect of the preamorphizing depth on the redistribution of boron atoms after annealing has also been investigated. Our results show that for ultrashallow junctions formed by ultra-low-energy ion implantation and spike RTA, the depth of the preamorphizing implant has very little impact on the junction depth. By optimizing the laser fluence and preamorphization depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 7 publications
2
47
0
1
Order By: Relevance
“…A similar phenomenon of the steplike dopant profile and its step movement was also observed in the Si substrate 7,8 during the LTP with the same wavelength but a higher fluence of 0.4 J / cm 2 and 0.5 J / cm 2 . The steplike dopant profile is attributed to the fact that the melting of the sample surface causes the diffusivity of dopant in the liquid phase to be much higher than that in the solid phase.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…A similar phenomenon of the steplike dopant profile and its step movement was also observed in the Si substrate 7,8 during the LTP with the same wavelength but a higher fluence of 0.4 J / cm 2 and 0.5 J / cm 2 . The steplike dopant profile is attributed to the fact that the melting of the sample surface causes the diffusivity of dopant in the liquid phase to be much higher than that in the solid phase.…”
supporting
confidence: 73%
“…The steplike dopant profile is attributed to the fact that the melting of the sample surface causes the diffusivity of dopant in the liquid phase to be much higher than that in the solid phase. 5,7 This melting phenomenon was monitored in this study by measuring the surface roughness of the Ge samples using an AFM. For the Ge substrates irradiated at a fluence of 0.16 J / cm 2 , the AFM analysis showed that the surface roughness root-mean-square value increased with the number of successive irradiation pulses from 3.9 Å ͑as-implanted͒ to 47.0 Å after five pulses, and to 71.2 Å after ten pulses.…”
mentioning
confidence: 99%
“…The flat shoulders indicate that very high B activations were achieved by annealing. Similar features have been observed in laser annealed samples [7]. However, we made no attempt to characterize the electronic property of junction, primarily due to the reason that currently existing techniques such as spreading resistance analysis are not reliable for ultra-shallow junctions.…”
Section: Resultssupporting
confidence: 65%
“…Driven by the need to further optimize/minimize thermal budget, various alternative thermal annealing processes, such as flash annealing [5], flame annealing [6], and laser annealing [7], have been seriously investigated. Considering factors such as repeatability, integrability and high throughput, flash annealing represents one of the most promising solutions for the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of shallow-melt LA in which the laser pulsed melts the Si surface and the molten region recrystallizes within tens of nanoseconds, (1) abrupt profile is formed with no dopant diffusion beyond liquid-solid interface, and (2) high dopant activation exceeding solid solubility is achieved (4)(5)(6)(7)(8). The junction depth is controlled by the melted depth, as diffusivity of boron in liquid phase is about eight orders higher than that in the solid phase (4,6). Boron atoms redistribute uniformly within the melt depth with negligible diffusion beyond liquid-solid interface.…”
mentioning
confidence: 99%